Diseño de una turbina a gas refrigerante sobrecalentado, para la generación de energía en un pozo petrolero en el Campo Caño Limón, Arauca (2020)
The current methodology for generating energy in an oil well in the Caño Limón Field, Arauca, has some problems that could cause a stop in oil production, and in addition to not being an eco-sustainable process; This allows venturing into alternative energies where the generation of electrical energy is proposed through an ORC (organic Rankine cycle), for which, when conducting a study it is concluded that the best alternative as a working fluid is R-134a refrigerant; Based on this power cycle, the design of a steam turbine is required. The types of conventional steam turbines are established, their respective structuring by systems and components, and their functional mode, in order to determine the best alternative for the design that is sought to be implemented in the development of this project, the latter, through a prioritization matrix to support the evaluation of alternatives. Based on the selected alternative, the detailed design of the superheated refrigerant gas turbine is carried out, where a mathematical analysis is carried out and in some cases by finite elements to guarantee the proposed design. On the other hand, the selection of the other components is made, such as bearings, labyrinth seals, valves, generator, couplings, QD bushing, among others, which are part of the turbine operating process.